2003
DOI: 10.1084/jem.20021788
|View full text |Cite
|
Sign up to set email alerts
|

Activation of Dendritic Cells through the Interleukin 1 Receptor 1 Is Critical for the Induction of Autoimmune Myocarditis

Abstract: Dilated cardiomyopathy, resulting from myocarditis, is the most common cause of heart failure in young patients. We here show that interleukin (IL)-1 receptor type 1–deficient (IL-1R1−/−) mice are protected from development of autoimmune myocarditis after immunization with α-myosin-peptide(614–629). CD4+ T cells from immunized IL-1R1−/− mice proliferated poorly and failed to transfer disease after injection into naive severe combined immunodeficiency (SCID) mice. In vitro stimulation experiments suggested that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
97
0
2

Year Published

2006
2006
2017
2017

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 142 publications
(105 citation statements)
references
References 39 publications
6
97
0
2
Order By: Relevance
“…Furthermore chronic, systemic administration of IL‐1 together with 6‐OHDA increases dopaminergic neuron loss and the number of MHC II‐positive cells (Pott Godoy et al, 2008). These data suggest that IL‐1β has a role in regulating MHC II responses after dopaminergic toxic insults, and mice null for the IL‐1 receptor 1 cannot activate CD4 + T‐cells (Eriksson et al, 2003). The IL‐1 β is probably derived from infiltrating MHC II‐monocytes.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore chronic, systemic administration of IL‐1 together with 6‐OHDA increases dopaminergic neuron loss and the number of MHC II‐positive cells (Pott Godoy et al, 2008). These data suggest that IL‐1β has a role in regulating MHC II responses after dopaminergic toxic insults, and mice null for the IL‐1 receptor 1 cannot activate CD4 + T‐cells (Eriksson et al, 2003). The IL‐1 β is probably derived from infiltrating MHC II‐monocytes.…”
Section: Discussionmentioning
confidence: 99%
“…We previously reported that Tlr4 mutant C3H/HeJ mice are resistant to development of EAM (45). Furthermore, IL-1 type 1 receptor signaling on DCs is critical for autoimmune myocarditis development (11). MyD88 is a crucial common adaptor molecule that mediates both TLRs and IL-1 type 1 receptor activation (46,47), and MyD88 signaling in DCs is critical for the induction of EAM (16).…”
Section: Discussionmentioning
confidence: 99%
“…EAM is a CD4 + T cell-mediated disease (7,14), and activation of self-Ag-loaded dendritic cells (DCs) is critical for expansion of autoreactive CD4 + T cells. Activation of TLRs and IL-1 type 1 receptor and their common downstream signaling adaptor molecule, MyD88, in self-Ag-presenting DCs is also critical for the development of EAM (11,15,16). Compared with inhibition of a single cytokine, a more effective treatment might be inhibition of various signaling pathways to induce production of cytokines through both innate and adaptive immunity.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Myocarditis severity was evaluated blinded by a clinical pathologist on a semiquantitative scale using grades from 0 to 4 as described previously [10] (0: no inflammatory infiltrates; 1: small foci of inflammatory cells between cardiomyocytes; 2: larger foci of >100 inflammatory cells; 3: >10 % of a cross-section involved; 4: >30% of a cross-section involved). For immunohistochemistry and immunofluorescence, OTC-embedded frozen hearts were fixed in acetone and then processed for antibody staining according to standard protocols.…”
Section: Histopathology and Immunohistochemistrymentioning
confidence: 99%